Almidón modificado de yuca como aditivo en fluidos de perforación base agua (2013)
The yucca starch was modified looking for an improvement in its thermal resistance and fluid loss control to be used as an additive in drilling fluids. The physical modification was made by pregelatinization and the chemical modification was made by cross linking with sodium tripoliphospate. An experimental design was used to find the best concentration of starch that minimizes the fluid filtrate, this concentration was 8 pounds per barrel. Two muds were formulated with 8 pounds per barrel of modified starch and paxcell LV (CMC) respectively to comparate their behavior; both of them showed a similar behavior, however the modified starch had a higher stability at high temperatures and pressures.